2002
DOI: 10.1007/bf02828188
|View full text |Cite
|
Sign up to set email alerts
|

Possible association of HLA-DRB1 gene with the autoantibody against myocardial mitochondria ADP/ATP carrier in dilated cardiomyopathy

Abstract: To probe the genetic background and immunopathogenesis of dilated cardiomyopathy (DCM) 77 patients with DCM, HLA-DRB1 gene polymorphism were analyzed by using the polymerase chain reaction/sequence specific primer (PCR/SSP) technique and autoantibody against myocardial mitochondria ADP/ATP carrier were examined by using the Immunoblot analysis. The frequency of HLA-DRB1*0901 allele was significantly higher in DCM patients in which autoantibody against ADP/ATP carrier of myocardial mitochondria is positive in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…This category often includes cardiomyopathy caused as a result of general systemic disorders where symptoms are not wholly associated with the heart [ 5 ]. HLA-DRB1*0901 allele has also been associated with a number of DCM patients, which suggested that mitochondrial ADP/ATP plays a large role in appropriate functionality of the heart [ 110 ]. It has also been shown that mitochondrial mutations are associated with changes in cardiomyopathy forms.…”
Section: Mitochondrial X Linked and Peripartum Cardiomyopathiesmentioning
confidence: 99%
“…This category often includes cardiomyopathy caused as a result of general systemic disorders where symptoms are not wholly associated with the heart [ 5 ]. HLA-DRB1*0901 allele has also been associated with a number of DCM patients, which suggested that mitochondrial ADP/ATP plays a large role in appropriate functionality of the heart [ 110 ]. It has also been shown that mitochondrial mutations are associated with changes in cardiomyopathy forms.…”
Section: Mitochondrial X Linked and Peripartum Cardiomyopathiesmentioning
confidence: 99%